2005
DOI: 10.1074/mcp.r500011-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Global Proteomic and Genomic Expression Profiles Generated from Islet α Cells

Abstract: Systematic profiling of expressed gene products represents a promising research strategy for elucidating the molecular phenotypes of islet cells. To this end, we have combined complementary genomic and proteomic methods to better assess the molecular composition of murine pancreatic islet glucagon-producing ␣TC-1 cells as a model system, with the expectation of bypassing limitations inherent to either technology alone. Gene expression was measured with an Affymetrix MG_U74Av2 oligonucleotide array, while prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…Third, our observation of proteins that were differentially expressed in the apparent absence of corresponding transcript may suggest rapid posttranslational degradation of transcript. Maziarz et al (30) found that 10% of proteins identified in mouse islet cells had no corresponding transcript, similar to the 12% we observed in our study. If these differences are not simply due to the limits of detection of microarray hybridization protocols, they merit additional examination because such proteins may represent factors important in regulating specific biological functions essential for postmating events, such as sperm storage and fertilization.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Third, our observation of proteins that were differentially expressed in the apparent absence of corresponding transcript may suggest rapid posttranslational degradation of transcript. Maziarz et al (30) found that 10% of proteins identified in mouse islet cells had no corresponding transcript, similar to the 12% we observed in our study. If these differences are not simply due to the limits of detection of microarray hybridization protocols, they merit additional examination because such proteins may represent factors important in regulating specific biological functions essential for postmating events, such as sperm storage and fertilization.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, although we cannot exclude experimental error as discussed in ref. 30, our observations suggest that some postmating changes in expression may be mediated by translation initiation or by posttranslational mechanisms such as targeted protein degradation (31). Third, our observation of proteins that were differentially expressed in the apparent absence of corresponding transcript may suggest rapid posttranslational degradation of transcript.…”
Section: Discussionmentioning
confidence: 79%
“…The ␣TC1-6 cell line has been used previously for gene profiling studies (33,34) and is preferable to primary islets, because ␣TC1-6 cells are an homogenous cell population (13), and the amount of RNA recovered from primary ␣-cells would be extremely limiting. Validation by Western blot showed for the first time that the expression of the SNARE proteins syntaxin 1A, SNAP-25, and VAMP-2 were regulated by glucose in ␣TC1-6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…We used Babelomics to find statistically over- and underrepresented GO categories in our oocyte proteome dataset. To compare the mouse oocyte proteome with other mouse tissue proteomes, we generated a combined database for the mouse based on the following mouse tissues and cell cultures characterized by LC-MS/MS: mouse heart [51], liver [51-53], brain [51,54], lung [51,55], kidney [51], spleen [56], placenta[51], cortical neurons cell culture[57], sperm [58], islet alpha-cell culture [59]. For enrichment analysis, our identified oocyte proteome was set as a test dataset and the combined mouse proteome was set as a reference.…”
Section: Methodsmentioning
confidence: 99%